2011
DOI: 10.1212/wnl.0b013e31821f46b8
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter assessment of cervical cord atrophy among MS clinical phenotypes

Abstract: Cervical cord atrophy provides a relevant and useful marker for the characterization of clinical heterogeneity of patients with MS. The stability of this measure among different centers supports its use as potential outcome measure to monitor disease progression in multicenter trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
129
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(157 citation statements)
references
References 33 publications
25
129
3
Order By: Relevance
“…We compute the volume of the segmented cord (vol) and use leave-out-one cross-validation to train our model and test on the omitted volume. As expected from the existing literature [1,7,8,12,16], we detect a moderate yet statistically significant correlation between volume and clinical score (vol: r=0.473, p=0.00824). The predictive ability for a linear regression model using volume as the explanatory variable is reported in Table 1 (row 1) and shown in Fig.…”
Section: Simple Linear Regression With Spinal Cord Volumesupporting
confidence: 87%
See 2 more Smart Citations
“…We compute the volume of the segmented cord (vol) and use leave-out-one cross-validation to train our model and test on the omitted volume. As expected from the existing literature [1,7,8,12,16], we detect a moderate yet statistically significant correlation between volume and clinical score (vol: r=0.473, p=0.00824). The predictive ability for a linear regression model using volume as the explanatory variable is reported in Table 1 (row 1) and shown in Fig.…”
Section: Simple Linear Regression With Spinal Cord Volumesupporting
confidence: 87%
“…Multiple sclerosis (MS) studies have found that a patient's physical disability correlates with spinal cord atrophy [1,7,8,12,16]. Measuring spinal cord atrophy is potentially useful for monitoring the progression of diseases or the effectiveness of therapies [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Differences in cervical cord volume and area among patients with different phenotypes of MS and healthy controls (HCs) measured by MR imaging have been identified in many studies. [2][3][4] Furthermore, a modest or strong correlation between spinal cord atrophy and disability has been demonstrated in numerous studies, suggesting that spinal cord atrophy is an essential determinant of clinical disability and a potential outcome measure to monitor MS disease progression. [5][6][7] The measurement of the upper cervical cord area is a well-established method for the assessment of spinal cord atrophy and has been applied in most studies so far.…”
mentioning
confidence: 99%
“…3,4 The MUCCA also has been measured recently on 3D T1-weighted MR images of the head covering the upper cervical cord, which has yielded promising results showing associations between MUCCA and clinical disability and disease progression. 2,5 Measuring the MUCCA from head MR images offers the opportunity to analyze MUCCA retrospectively in datasets without dedicated cervical 3D T1-weighted images, and it can reduce costs and patient burden in prospective studies by eliminating the need for separate cervical cord image acquisitions if these are only acquired to measure the MUCCA.…”
mentioning
confidence: 99%